Przemiany pierwotnych wierzeń dotyczących świata zmarłych w Biblii hebrajskiej na tle wierzeń bliskowschodnich - Münnich, Maciej
Transformations of Primitive Beliefs Concerning the World of the Dead in the Hebrew Bible Against the Background of Near Eastern Beliefs; engl. Resümee